Considerações ecológicas do manguezal da Laguna de Jacarapé, João Pessoa, PB e as interferências antrópicas na sua área de influência - Soares, Dario Manoel Barroso (2000)
The mangrove studied is located on the southern coast of the municipality of João Pessoa, Paraíba and is located in the micro-basin of Jacarapé, between the geographic coordinates of 7º 11’ 30” and 7º 12’ 00” of south latitude and 34º 47' 45” and 34º 48' 07” of west longitude, limited to the north by the Aratú River basin and to the south, by the Cuiá River basin. This work aimed to evaluate the current state of the basic ecological characteristics of the Jacarapé mangrove, by determining its structural aspects and levels of productivity and decomposition of organic matter, as well as characterizing the main human interferences in its area of influence with the use of environmental impact matrices and through a socio-environmental diagnosis with users of the fluvial-marine plain. The study of the structural characteristics of the mangrove was carried out using plot methods. To obtain the productivity indices, randomly distributed nylon collectors were used inside the mangrove. The values obtained from the dry weight of the samples were converted into gC.m-2.day-1. Studies on in situ leaf decomposition were carried out using nylon bags with a 1.5 mm mesh opening. The socio-environmental diagnosis of users in Jacarapé was obtained from the application of structured and semi-structured questionnaires and informal interviews. For the study of anthropogenic interference, environmental impact matrices were applied in four (04) distinct sub-areas of the mangrove. Such sub-areas were determined based on analysis of aerial photos and through periodic visits to study sites. The mangrove studied is basically constituted by the species Rhizophora mangle, Laguncularia recemosa, Conocarpus erectus and the species A. glabra, the latter considered atypical in mangroves. In general, the studied mangrove vegetation proved to be well structured, with Rhizophora mangle as the most representative species. The highest densities (maximum of 3,540 individuals/ha, in transection 4), IVIe (282.2 – transection 4) and IVCe (198.9 – transection 4) were recorded for the species R. mangle. The maximum values of basal area (19.2m2/ha), Diameter at Chest Height (DBH) equal to 23 cm and height (12 m) were recorded in transection 02. Regarding seedlings and young plants, these were more abundant in the transection 04. Comparatively, transection 03 was the one with the highest mortality values (61.5%) and partial or total cuts (57.1%) among all analyzed transections. The highest values of litter productivity occurred in September (2.29g Cm-2.day-1) and October (2.34g Cm-2.day-1), and the lowest index occurred in May (0.65 g C.m-2.day-1). The high rates of litter productivity and the intense decomposition process observed, especially in relation to the species R. mangle, suggest high metabolic rates, probably reflecting on its structural characteristics. The decomposition rate was generally high in the first 30 days of the experiment. The socio-environmental diagnosis carried out with the owners of tents (bars) and users of the coastal lagoon system, pointed out at least two interferences caused by their presence in the environment. One of them is about the disorderly occupation of the coastal plain by the owners of shacks and the other concerns the large amount of solid waste (garbage) left by the inhabitants of the place. In addition to these interferences, the opening of trails, canalization, vegetation cuts, organic waste disposal, fires, among other aggressions to the studied environment, were also detected in the subareas of study. In short, the disorderly occupation of the Jacarapé coastal plain by tent owners, in addition to the expasion of recreational and tourist activities, combined with the state government’s tourism project, has generated a series of impacts that end up interfering with the availability of natural resources and in the environmental quality of the Jacarapé mangrove.